-6(n-2)-1=-(4+7n)

Simple and best practice solution for -6(n-2)-1=-(4+7n) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -6(n-2)-1=-(4+7n) equation:


Simplifying
-6(n + -2) + -1 = -1(4 + 7n)

Reorder the terms:
-6(-2 + n) + -1 = -1(4 + 7n)
(-2 * -6 + n * -6) + -1 = -1(4 + 7n)
(12 + -6n) + -1 = -1(4 + 7n)

Reorder the terms:
12 + -1 + -6n = -1(4 + 7n)

Combine like terms: 12 + -1 = 11
11 + -6n = -1(4 + 7n)
11 + -6n = (4 * -1 + 7n * -1)
11 + -6n = (-4 + -7n)

Solving
11 + -6n = -4 + -7n

Solving for variable 'n'.

Move all terms containing n to the left, all other terms to the right.

Add '7n' to each side of the equation.
11 + -6n + 7n = -4 + -7n + 7n

Combine like terms: -6n + 7n = 1n
11 + 1n = -4 + -7n + 7n

Combine like terms: -7n + 7n = 0
11 + 1n = -4 + 0
11 + 1n = -4

Add '-11' to each side of the equation.
11 + -11 + 1n = -4 + -11

Combine like terms: 11 + -11 = 0
0 + 1n = -4 + -11
1n = -4 + -11

Combine like terms: -4 + -11 = -15
1n = -15

Divide each side by '1'.
n = -15

Simplifying
n = -15

See similar equations:

| -11n^2=9-2n | | 54m= | | 14g-5g-5g-3G=17 | | -3-3r=-6(5+5r) | | x^2-13x+39=3 | | x^2=3x-28 | | 3x-5=7x-45 | | -33-2b=-5+8(1-b) | | 2w-w+4w+w-5w=8 | | 5x+4=2y | | 6(4m-6)=30+2m | | sin(3x)-sin(7x)=0 | | -2x+17=-6(x+1)-5 | | 3m-2m-m+m=7 | | (1-3x)(9x-7)=0 | | -10x+8y=10 | | (x+1)2=144 | | 16+4r=7r+7 | | 15s-6s-6s=18 | | -8+5a=-93 | | 9x^2+4=-77 | | 5x+6y=226.19 | | 4x^2-25x+27=-4x+7 | | 27+x=68 | | 4s-3s=4 | | 2-10i+5x=17-5yi | | 6k-3=-93 | | y+4=4(x-3) | | 8n+n=8 | | (2x+5y)(x^2+4xy-5y^2)= | | 10+4a^2=26 | | 15h-12h=15 |

Equations solver categories